Parent-Child Secure Attachment Relationship with Academic Self-Regulation in Grade 10 Students of Vocational High Schools in Sidoarjo: Hubungan Secure Attachment Orangtua-Anak dengan Regulasi Diri Akademik pada Siswa Kelas 10 Sekolah Menengah Kejuruan di Sidoarjo - Afrilliyanti, Riris Ayu; Affandi, Ghozali Rusyid (Indonesian Journal of Innovation Studies, 2023)
Adolescence is referred to as the period of self-discovery, where they begin to be sensitive to the environment around them. What happens in his environment and what is done by those around him greatly affects the formation of his personality. Researchers obtained data from BK teachers that there was an Academic Self-Regulation problem in students. The purpose of this study was to find out the relationship between Parent-child Secure Attachment and Academic Self-Regulation in X-grade students at SMK Negeri 1 Jabon. The study used quantitative approaches to correlation methods. The subjects in this study were students of class X smk Negeri 1 Jabon taken with nonprobability sampling techniques. The population of the study was grade X students and sample-setters from the research population used Isaac and Michael's table with a 5% error rate, bringing the total to 131 students. Data collection techniques use the psychology scale, namely the Parent-Child Secure Attachment scale and the Academic Self-Regulation scale. Data analysis technique uses the correlation of pearson product moment using computer assistance, using the SPSS 23 for windows program. Based on the results of the data analysis showed that there was a significant positive relationship in Secure Attachment Parent-child and Academic Self-Regulation in SMK Negeri 1 Jabon. Based on the results of the correlation test known significance value of 0.000 because the value sig <0.05 then there is a relationship between variable X and Y and strengthened by the results of the analysis that the influence of variable X contributes effectively 50.2% to variable Y. The results show that the higher secure attachment of parents-children then the higher the academic self-regulation of students and vice versa if secure attachment parents-children are low then the student's Academy Self Regulation also low.